Increasing EFL Learners’ Oral Production at a Public School Through Project-Based Learning (2017)
This research study examined how a group of ninth graders enhanced the speaking skill in an English as a foreign language classroom through project-based learning. Data about the experience were collected through field notes, transcripts of learners’ oral performance, and one interview. Grounded theory was implemented for data analysis, out of which three main findings emerged: (1) project-based learning encouraged students to increase oral production through lexical competence development, (2) helped them to overcome fears of speaking in L2, and (3), increased their interest in learning about their school life and community.